The Effect of Functional Disability and Quality of Life on Decision to Have Surgery in Patients With Lumbar Disc Herniation. (July 2018) - Yılmaz, Emel; Çıkrıkçıoğlu, H. Yağmur; Baydur, Hakan
Abstract : BACKGROUND/PURPOSE: This study aimed to determine the effect of functional disability and quality of life (QoL) on the decision to have surgery in patients with lumbar disc herniation (LDH). METHOD/DESIGN: This is descriptive and cross-sectional survey. A total of 239 patients were included in the study. Data were collected using a personal information form, Surgical Belief and Attitudes Questionnaire (SBAQ), Visual Analog Scale (VAS), Oswestry Disability Index (ODI), Roland–Morris Disability Questionnaire (RMDQ) and Short Form-36 (SF-36). The data analysis was undertaken using Mann–Whitney U test, χ 2 test, and logistic regression model. RESULTS: Patients were found to have low mean scores in the SF-36 subscales and SBAQ and high mean scores in ODI, RMDQ, and VAS. Six weeks after the first interview, 48.1% of patients decided to undergo surgery. A statistically significant difference was found between a decision to have surgery and the ODI, RMDQ, VAS, SBAQ scores and 6 of the 8 SF-36 subscales (except for role physical and general health; p < .05). Patients who had higher functional disability, pain intensity, and SBAQ score and those with lower QoL were more likely to decide to undergo surgery. CONCLUSIONS: The results of the study showed that patients with LDH who have been referred for surgery experience high functional disability and pain and a poor QoL, and that these factors have an impact on their decision to have surgery process.